Living and Learning With Integrity: A Pushing and Pulling Ground for Teachers (Social Inquiry: Journal of Social Science Research, 2023)
Teacher integrity is crucial for maintaining their own sense of ethical identity, professionalism, developing institutional culture of learning and sustainable development of schools. However, there are several elements related to socio-cultural norms, values and practices that support or resist the effective adoption of integrity at schools and in day to day life. This study explores how teachers’ professional integrity is shaped and practised at schools. Following the qualitative study design, I employed mostly literature review substantiated by in-depth interviews with six teachers from two schools in Kavre district. The findings reveal that school culture determines integrity of teachers. School environment, prescribed rights and duties of teachers and headteacher’s leadership shape the integrity of teachers. The social settings and its ingredients are pushing and pulling grounds that teachers address duly for effective implementation of integrity at schools. Since integrity is a social phenomenon deeply rooted in socio-cultural practices, the state needs to come up with more sensitive and inclusive code of conduct for responsive behaviours and better results that are contextually developed through the continuous participation of the concerned stakeholders of the schools.